2014
DOI: 10.1111/omi.12039
|View full text |Cite
|
Sign up to set email alerts
|

A role for the DtxR family of metalloregulators in gram‐positive pathogenesis

Abstract: SUMMARY Given the central role of transition metal ions in a variety of biochemical processes, the colonization, survival, and proliferation of a bacterium within a host hinges upon its ability to overcome the metal ion deprivation that characterizes nutritional immunity. Metalloregulatory, or “metal-sensing” proteins have evolved in bacteria to mediate metal ion homeostasis by activating or repressing the expression of genes encoding metal ion transport systems upon binding their cognate metal ion. Yet increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 54 publications
1
43
0
Order By: Relevance
“…It has been demonstrated that transcription of genes encoding Mn 2+ -specific SBPs in multiple streptococcal species is repressed by Mn 2+ (Crump et al 2014; Merchant and Spatafora 2014; Ogunniyi et al 2010). In each case, this repression is mediated by a MntR-like protein often encoded within the ABC transporter operon or nearby.…”
Section: Biological Functions Of Mn2+ In Streptococcimentioning
confidence: 99%
“…It has been demonstrated that transcription of genes encoding Mn 2+ -specific SBPs in multiple streptococcal species is repressed by Mn 2+ (Crump et al 2014; Merchant and Spatafora 2014; Ogunniyi et al 2010). In each case, this repression is mediated by a MntR-like protein often encoded within the ABC transporter operon or nearby.…”
Section: Biological Functions Of Mn2+ In Streptococcimentioning
confidence: 99%
“…This effect may partly explain the increase of expression of scaCBA in the presence of toxic levels of Zn 2ϩ (85) (88). Later studies showed that SloR controls a large regulon, acting both as a repressor and as an activator (69,89). The homologous regulator MtsR of S. pyogenes also controls a large regulon that includes the genes encoding the Mn 2ϩ and Fe 2ϩ transporter MtsABC (90,91).…”
Section: One-component Systemsmentioning
confidence: 99%
“…Resistance mechanisms against metals are not well characterized for LAB (reviewed in reference 26), and most available information concerns pathogenic streptococci. In bacteria, three types of metalsensing transcriptional regulators control gene expression in response to metal ion concentrations: derepressors (ArsR-SmtB, CopY, and CsoR-RcnR families), activators (MerR family), and corepressors (Fur, NikR, and DtxR families) (69).…”
Section: One-component Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…(12,13) The dtxR gene is also referred as a global regulator or metalloregulator as its function in regulating several genes involved in iron uptake and transport, including Siderophore or Corynebactin. (14,15) The DtxR is a 25 kDa protein that consists of 226 amino acid residues. DtxR proteins are divided into three domains, helix-turn-helix (residues 1-73), metal binding site (residues 74-140), and Src homology 3 (SH-3) (residues 147-226).…”
Section: ) Worldmentioning
confidence: 99%